Decision making, impulsivity, and addictions: do Parkinson's disease patients jump to conclusions? - Djamshidian,A; O'Sullivan,SS; Sanotsky,Y; Sharman,S; Matviyenko,Y; Foltynie,T; Michalczuk,R; Aviles-Olmos,I; Fedoryshyn,L; Doherty,KM; Filts,Y; Selikhova,M; et al. (Mov Disord, 2012)
Links between impulsive-compulsive behaviors (ICBs) in treated Parkinson's disease (PD), behavioral addictions, and substance abuse have been postulated, but no direct comparisons have been carried out so far. We directly compared patients with PD with and without ICBs with illicit drug abusers, pathological gamblers, and age-matched healthy controls using the beads task, a test of reflection impulsivity, and a working memory task. We found that all patients with PD made more impulsive and irrational choices than the control group. PD patients who had an ICB showed similar behavior to illicit substance abusers, whereas patients without ICBs more closely resembled pathological gamblers. In contrast, we found no difference in working memory performance within the PD groups. However, PD patients without ICBs remembered distractors significantly less than all other patients during working memory tests. We were able to correctly classify 96% of the PD patients with respect to whether or not they had an ICB by analyzing three trials of the 80/20 loss condition of the beads task with a negative prediction value of 92.3%, and we propose that this task may prove to be a powerful screening tool to detect an ICB in PD. Our results also suggest that intact cortical processing and less distractibility in PD patients without ICBs may protect them from developing behavioral addictions.